Penyuluhan dengan Media Tiga Dimensi Terhadap Perubahan Pengetahuan, Sikap, Tindakan Konsumsi Buah dan Sayur - Liva Rahayu Suprihantini; Desak Putu Sukraniti; A.A.Gde Raka Kayanaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
The prevalence of lack of fruit and vegetable consumption in the age group 10 years in 2013 is 93.5%. The factor causes this is the lack of knowledge about fruits and vegetables. This study aims to determine the effectiveness of counseling with three-dimensional media on changes in fruit and vegetable consumption behavior in MI Tawakkal Denpasar. Type of Quazi Experiment research with the design of one group pre-posttest. The sample is grade 4 and 5 students taken by purposive sampling, as many as 104 students. Data collection is done by interviewing using a questionnaire. The statistical analysis used was the Wilcoxon Test. The results showed that the average knowledge before counseling was 8.28 and after counseling 9.56 with the results of the analysis there was a significant difference between knowledge about fruits and vegetables before and after counseling (p = 0,000). Average attitudes before counseling were 36.19 and after counseling 37.42 with the results of the analysis there were significant differences between attitudes about fruit and vegetables before and after counseling (p = 0,000) Average consumption of fruits and vegetables before counseling 3.28 and after counseling 3.88 with the results of the analysis there was a significant difference between fruit and vegetable consumption measures before and after counseling with three-dimensional media (p = 0,000). In conclusion, counseling with three-dimensional media was effective towards changing knowledge of fruit and vegetable consumption attitudes and actions in MI Tawakkal Denpasar.Keywords: Consumption, Fruit, Vegetables